ANALISIS INVESTASI DAN KONTRIBUSI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN MERANGIN PROVINSI JAMBI DENGAN MENGGUNAKAN PENDEKATAN ICOR - Suandi Suandi; Arman Delis (University of Jember, 2020)
The research objective: (1) analyzing the investment and economics of Merangin Regency, (2) analyzing the contribution of the agricultural sektor to the economics of Merangin Regency, Jambi Province. The data used are series data from 2010-2014. Data were analyzed through the Incremental Capital Output Ratio (ICOR) approach. The results showed that during the 2011-2014 period, the largest investment was made in the agricultural sektor which reached 37.45 percent, then followed by the trade sektor and the manufacturing sektor, respectively 28.00 and 16.80 percent. The average ICOR rate for the period 2010-2014 was 9.41. The 2015 ICOR score is better than the previous year's ICOR value. The agricultural sektor has the lowest ICOR and is followed by the transportation sektor; construction; finance; and the service sektor so that the agricultural sektor has a positive and efficient impact on investing. The analysis shows that the agricultural sektor has a contribution to the economic of Merangin Regency.